St. Vincent and the Grenadines. Annual report 2008 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
Presents the results of IICA in St. Vincent and the Grenadines in 2008 in relation to the state of agriculture and rural life, the implementation of the national technical cooperation agenda, interagency cooperation, horizontal technical cooperation, new opportunities for technical cooperation, and the organized activities